Endoscopic ultrasound‐guided hepaticogastrostomy for hepaticojejunostomy stricture using a one‐step stent deployment technique (with video). (6th November 2020) - Ogura, Takeshi; Okuda, Atsushi; Higuchi, Kazuhide
Abstract : Highlight A novel, fully covered, self‐expandable metal stent with a fine‐gauge stent delivery system has recently become available in Japan. Ogura and colleagues describe the technical procedure of endoscopic ultrasound‐guided hepaticogastrostomy using a one‐step stent deployment technique without fistula dilation, which is clinically useful and may help prevent adverse events.